Commercial Bank Lending: Process, Credit Scoring, and Costs of Errors in Lending - Altman, Edward I. (Journal of Financial and Quantitative Analysis, 1980)
Edward I. Altman, Commercial Bank Lending: Process, Credit Scoring, and Costs of Errors in Lending, The Journal of Financial and Quantitative Analysis, Vol. 15, No. 4, Proceedings of 15th Annual Conference of the Western Finance Association, June 19-21, 1980, San Diego, California (Nov., 1980), pp. 813-832